Late-term Effects of Surgery on Nasal Functions in Patients who Underwent Total Laryngectomy Surgery - Karaoglu,Deniz (2017)
Abstract Introduction There is a common opinion that losing airway functions in total laryngectomy patients cause changes in nasal physiological rates. Studies conducted to review the subject present gaps, especially in terms of objective measurements. Objective We evaluated late-term effects of surgery on nasal functions in patients who underwent total laryngectomy surgery more than two years ago. Methods We included in the study 22 patients who had undergone total laryngectomy, as well as 24 healthy subjects with similar demographic characteristics as the control group. We performed acoustic rhinometry for intranasal volume and cross-sectional area measurements, saccharin test formeasurement of nasalmucociliary clearance, and smell identification test for evaluation of olfactory function in the patient and control groups. We compared and statistically analyzed the data obtained from the groups. Results In our study, although late-term (>2 years) measurements were not statistically significant, we detected more nasal passage patency in the patient group than in the control group. In smell identification test, lower scores were obtained in the patient group. The difference between measurements in both groups was statistically significant. Conclusion We believe that since the upper respiratory tract is disabled due to tracheostomy in patients with total laryngectomy, atrophy occurs in the late term and, consequently, nasal mucociliary clearance is impaired. We also see diminished olfactory function in total laryngectomy patients.